2020
DOI: 10.1055/s-0039-3400491
|View full text |Cite
|
Sign up to set email alerts
|

Use of Direct Oral Anticoagulants in Children and Adolescents

Abstract: While the need for anticoagulation in children has increased over the last decades, dose regimens of currently used anticoagulants, including low-molecular-weight heparin (LMWH) and vitamin K antagonist (VKA), are still extrapolated from adult guidelines because well-designed clinical trials were never performed in children. This approach is not optimal due to specific pediatric features of the hemostatic system and pathophysiology of thrombosis. These anticoagulants also present several disadvantages that fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 36 publications
0
15
0
3
Order By: Relevance
“…Another trial assessed the safety and efficacy of rivaroxaban in central venous thrombosis compared with standard of care, and no differences were evident between the two treatments in recurrences and bleeding risks [121]. Trials in pediatric populations evaluating the safety and efficacy of other factor Xa inhibitors (edoxaban and apixaban) are also ongoing [122][123][124][125].…”
Section: Direct Oral Anticoagulantsmentioning
confidence: 99%
“…Another trial assessed the safety and efficacy of rivaroxaban in central venous thrombosis compared with standard of care, and no differences were evident between the two treatments in recurrences and bleeding risks [121]. Trials in pediatric populations evaluating the safety and efficacy of other factor Xa inhibitors (edoxaban and apixaban) are also ongoing [122][123][124][125].…”
Section: Direct Oral Anticoagulantsmentioning
confidence: 99%
“…This important field is discussed by Dr Albisetti. 7 Similarly, oral anticoagulant therapy in geriatric patients remains a challenge in daily practice. Drs Herold and Bauersachs point out pitfalls and areas of uncertainty in treating this constantly growing patient population.…”
Section: Dear Colleaguesmentioning
confidence: 99%
“…Direct oral anticoagulants can be administered orally, are antithrombin independent, have a rapid onset and offset of action, few drug and food interactions, and predictable pharmacokinetics with no need of routine monitoring of anticoagulation activity. 17 Recently, two phase 3 direct oral anticoagulant trials for paediatric venous thromboembolism have been published. 18,19 The rivaroxaban phase 3 study showed that rivaroxaban was as safe and effective as standard anticoagulants in children with venous thromboembolism.…”
mentioning
confidence: 99%